2020
DOI: 10.3389/fvets.2020.00651
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to LCA Evaluation of Lamb Meat Production in Two Different Breeding Systems in Northern Italy

Abstract: Lamb meat production provides vital landscape-management and ecosystem services; however, ruminant farming produces a considerable share of the world's greenhouse gas emissions. To measure and compare the advantages and disadvantages of the intensification of livestock farming, an integrative analysis was conducted in this study by combining environmental impact analysis and animal welfare assessment. This approach is the first of its kind and is the innovative aspect of this paper. The methodology of Life Cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, it is shown that extensive sheep farms have a significantly lower impact in terms of local impact factors like eutrophication and acidification [3,50]. In this respect, the findings regarding EP for breeds in extensive conditions in the trial conducted in Turkey were lower than those of other sheep production systems in Europe [11,50]. In Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it is shown that extensive sheep farms have a significantly lower impact in terms of local impact factors like eutrophication and acidification [3,50]. In this respect, the findings regarding EP for breeds in extensive conditions in the trial conducted in Turkey were lower than those of other sheep production systems in Europe [11,50]. In Fig.…”
Section: Discussionmentioning
confidence: 97%
“…As a result, the meat industry induces approximately 80% of agricultural-based emissions. Intensive agriculture has been encouraged to reduce CO 2 emissions [11][12][13][14]. Hereby, the aim of the study is to assess the environmental impact of three sheep management systems in terms of global warming potential, acidification potential, eutrophication potential, and land use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, they are measured in plasma and serum. Still, it is considered preferable to measure them in other biological matrices including saliva, urine, feces, and hair because these matrices can be sampled without the risk of inducing a glucocorticoid response [5]. Moreover, the techniques of sampling and analysis available are feasible and practical for measuring to be performed both at an individual and group level [6].…”
Section: Introductionmentioning
confidence: 99%